Why You Gotta Be So Mean? Examining The Impact Of Underlying Social Factors On Traditional And Cyberbullying Offending - Strohacker, Emily (2017)
Instances of traditional school yard bullying among adolescents have been examined by researchers for decades. More recently, cyberbullying has been introduced among adolescents and has begun to be seen as a counterpart to traditional offending behaviors. Scholars have examined the rates of these types of offending, as well as the negative outcomes that result from victimization. However, studies examining the underlying factors that lead to these types of offending, specifically a comparison and combination of the two, are few and far between. This research examines how factors of strain, association with deviant peers, alcohol and/or drug use, and time spent with friends may influence an adolescent's likelihood to engage in any or all offending behaviors. Data are from the Health Behavior in School-Aged Children for which a national sample of 12,642 adolescents aged 10 to 17 years, in grades 5 through 10 were surveyed during the 2009-2010 school year, to assess behaviors that have been linked to health-risks among adolescents. Results indicate that specific factors of strain, drug and/or alcohol use, deviant peers, and time spent with peers significantly impact cyberbullying offending, traditional bullying offending, and both types of offending combined, among adolescents. The findings show that further action should be taken to reduce rates of all types of bullying among adolescents in schools and homes